The Implementation of Village-Owned Enterprise Program - P, Resky Amalia; Tamrin, Saddam Husain (Departemen Ilmu Administrasi FISIP UNHAS, 2021)
The purpose of this study is to analyze and identify the implementation of Village-Owned Enterprises (BUMDes) program policies in Sabbangparu District, Wajo Regency and identify supporting and inhibiting factors in implementing Village-Owned Enterprises (BUMDes) programs in Sabbangparu District. This research is conducted by looking at the implementation of the theory proposed by Grindle 1980, which is from the contents of the policy and the implementation environment of this study using a qualitative descriptive approach. It intended to provide a clear picture of the problem under study and systematically explain the data in implementing the BUMDes program. Research results on the implementation of BUMDes are seen from the content and context variables. The implementation of the BUMDes is still not running effectively due to the lack of support from the community in implementing the BUMDes. In addition, there is still insecurity from village leaders in running BUMDes and a lack of supporting the administration.